Comparison of differentiation protocols of SH-SY5Y cells for use as an in vitro model of Alzheimer’s disease - Steenkamp, Vanessa (University of Pretoria, 2021)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2021.